1984
DOI: 10.1037/0033-2909.96.3.435
|View full text |Cite
|
Sign up to set email alerts
|

Acute psychophysiologic reactivity and risk of cardiovascular disease: A review and methodologic critique.

Abstract: Recent behavioral and biomedical research has suggested that psychophysiologic responsiveness (reactivity) to emotional stress may be a marker of processes involved in the development of cardiovascular disorders. The assessment of reactivity focuses on acute changes in functioning as opposed to the sole assessment of resting levels of variables. This article reviews evidence linking behaviorally induced cardiovascular and endocrine changes to coronary heart disease and essential hypertension. Particular attent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
508
1
14

Year Published

1986
1986
2003
2003

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 952 publications
(539 citation statements)
references
References 126 publications
16
508
1
14
Order By: Relevance
“…We commonly investigate these processes using acute laboratory stress models in which subjects are exposed to difficult cognitive, &ocial, or psychomotor tasks such as mental arithmetic and public speaking (4). These models are thought to be successful since these tasks consistently elicit elevations in heart rate (HR) and blood pressure (BP) and in circulating levels of epinephrine and norepinephrine (5). Although we view these tasks as psychological stressors, other aspects of the tasks may contribute to the quantity and quality of physiological response.…”
Section: Introductionmentioning
confidence: 99%
“…We commonly investigate these processes using acute laboratory stress models in which subjects are exposed to difficult cognitive, &ocial, or psychomotor tasks such as mental arithmetic and public speaking (4). These models are thought to be successful since these tasks consistently elicit elevations in heart rate (HR) and blood pressure (BP) and in circulating levels of epinephrine and norepinephrine (5). Although we view these tasks as psychological stressors, other aspects of the tasks may contribute to the quantity and quality of physiological response.…”
Section: Introductionmentioning
confidence: 99%
“…These effects have been observed in animals (Manuck, Kaplan, & Clarkson, 1983a;1985a) and also in acute and chronic studies of humans (Frankenhaeuser, 1983;Henry, 1983;Herd, 1981;Schneiderman, 1983), primarily using male subjects. Coronary heart disease (i.e., angina, myocardial infarction) results when arterial obstruction or atherosclerosis becomes severe enough to block blood supply to the heart (Krantz & Manuck, 1984). …”
mentioning
confidence: 99%
“…Upon sacrifice, those monkeys whose psychosocial stress had resulted in high physiological reactivity showed the most advanced state of atherosclerosis. Likewise, in retrospective studies of men and women (e.g., The Framingham Heart Study, Haynes, Levine, Scotch, Feinleib, & Kannel, 1978), elevated physiological reactivity to laboratory stressors has been noted in patients with coronary heart disease or hypertension (Krantz & Manuck, 1984).A number of investigators (Folkow, Hallback, Lundgren, Silverttson, & Weill, 1973;Von Eiff, 1970) have hypothesized that such reactivity may be heritable. Studies have found that young normotensive individuals tend to manifest greater elevations in blood pressure during stressful situations when there is a family history of hypertension (Briggs & Oerting, 1937;Brod, 1960;Shapiro, 1961 testing.…”
mentioning
confidence: 99%
“…Everson, Goldberg, Kaplan, Julkunen, & Salonen, 1998;Porter, Stone & Schwartz, 1999;Arrighi et al, 2000). It has been presented either as a marker of pathogenic processes in atherosclerosis or as playing a role in its development (Krantz & Manuck, 1984). For example, in a recent study, Krantz et al (1999) found that among a group of cardiac patients, the patients higher in diastolic blood pressure response to stress were more likely to have cardiac events over a follow-up period of 3.5 years.…”
Section: Cardiovascular Reactivity and Coronary Artery Diseasementioning
confidence: 99%